An application‐oriented roadmap to select polymeric nanocomposites for advanced applications: A review. Issue 4 (24th December 2019) - Doagou‐Rad, Saeed; Islam, Aminul; Merca, Timea D.
Abstract: Polymeric nanocomposites are the materials incorporating nanosized inclusions into the polymer matrixes. The result of the addition of nanoparticles/fibers is a drastic improvement in properties that may include mechanical, electrical, thermal conductivity, or even the acoustical properties. Polymer nanocomposites have spawned huge interest for the development of high‐performance products such as lightweight sensors, thin‐film capacitors, batteries, flame retardant products, biodegradable and biocompatible materials, and so on. The field of polymer nanocomposites has been at the forefront of research in the polymer community for the past few decades and an extremely large number of scientific papers have been published. Nevertheless, application‐oriented guidelines for selecting the ecofriendly nanocomposites for advanced industrial applications are missing in the state of the art. This review article summarizes the current state‐of‐the‐art polymeric nanocomposites, highlighting prominent nanofillers categorized based on their applications, origins, dimensional characteristics, and so on. Each filler type contains a short description of its main feature together with the most relevant and potential applications. To address the global concern about nondegradable wastes, novel green alternatives of each nanofiller type are discussed. Special attention is also given to the biocompatibility properties of the composites. This study provides a state‐of‐the‐art road map to select multifunctional polymeric nanocomposites from huge varieties for advanced industrial applications.